Visual-area coding technique (VACT): optical parallel implementation of fuzzy logic and its visualization with the digital-halftoning process - Konishi, T; Tanida, J; Ichioka, Y (Applied optics (2004), 1995)
A novel technique, the visual-area coding technique (VACT), for the optical implementation of fuzzy logic with the capability of visualization of the results is presented. This technique is based on the microfont method and is considered to be an instance of digitized analog optical computing. Huge amounts of data an be processed in fuzzy logic with the VACT. In addition, real-time visualization of the processed result can be accomplished.